Characterization of Ras k 1 a novel major allergen in Indian mackerel and identification of parvalbumin as the major fish allergen in 33 Asia‐Pacific fish species. Issue 4 (15th January 2018) - Ruethers, T.; Raith, M.; Sharp, M. F.; Koeberl, M.; Stephen, J. N.; Nugraha, R.; Le, T. T. K.; Quirce, S.; Nguyen, H. X. M.; Kamath, S. D.; Mehr, S. S.; Campbell, D. E.; et al.
Summary: Background: Fish is a well‐recognized cause of food allergy and anaphylaxis. The evolutionary and taxonomic diversity of the various consumed fish species pose a challenge in the identification and characterization of the major fish allergens critical for reliable diagnostics. Globally, fish is a rising cause of food allergy complicated by a large under‐investigated variety of species as well as increasing global tourism and trade. This is the first comprehensive study on allergen profiles of heat‐processed fish from Vietnam. Objective: The aim of this study was to identify the major heat‐stable allergens from frequently exported Asia‐Pacific freshwater and marine fish and to characterize the major allergen parvalbumin (PV) from one of the most consumed and exported fish species from Asia, the Indian mackerel ( Rastrelliger kanagurta ). Methods: Heated protein extracts from 33 fish species were separated by gel electrophoresis. PV isoforms were identified by immunoblotting utilizing 3 different PV‐specific monoclonal and polyclonal antibodies and further characterized by mass spectrometry. IgE reactivity was investigated using sera from 21 patients with confirmed fish allergy. Results: Heat‐stable IgE‐reactive PVs, with up to 5 isoforms per species, were identified in all 33 analysed fish species. In the Indian mackerel, 7 PV isoforms were identified by 2D‐gel electrophoresis combined with mass spectrometric analyses. The amino acid sequence deduced from cDNA of the most expressed isoform showed a high identity (>90%) to PVs from 2 other mackerel species. Conclusions and Clinical Relevance: Different PVs were identified as the major heat‐stable allergens in all 33 analysed freshwater and marine fish species from Vietnam, many of which are exported world‐wide and 21 species that have never been investigated before. The Indian mackerel PV represents a novel fish allergen, now officially registered as Ras k 1. Improved diagnostics for fish allergy against Asia‐Pacific species should be developed with focus on PV.